Renal Expression and Urinary Excretion of Na-K-2Cl Cotransporter in Obstructive Nephropathy - Brandoni, Anabel (2017)
Renal damage due to urinary tract obstruction accounts for up to 30% of acute kidney injury in paediatrics and adults. Bilateral ureteral obstruction (BUO) is associated with polyuria and reduced urinary concentrating capacity. We investigated the renal handling of water and electrolytes together with the renal expression and the urinary excretion of the Na-K-Cl cotransporter (NKCC2) after 1 (BUO-1), 2 (BUO-2), and 7 (BUO-7) days of release of BUO. Immunoblotting and immunohistochemical studies showed that NKCC2 expression was upregulated in apical membranes both from BUO-2 and from BUO-7 rats. The apical membrane expression, where NKCC2 is functional, may be sufficient to normalize water, potassium, sodium, and osmolytes tubular handling. NKCC2 abundance in homogenates and mRNA levels of NKCC2 was significantly decreased in almost all groups suggesting a decrease in the synthesis of the transporter. Urinary excretion of NKCC2 was increased in BUO-7 groups. These data suggest that the upregulation in the expression of NKCC2 in apical membranes during the postobstructive phase of BUO could contribute to improving the excretion of sodium and consequently also the excretion of potassium, osmolytes, and water. Moreover, the increase in urinary excretion of NKCC2 in BUO-7 group could be a potential additional biomarker of renal function recovery.